Public Criminology in an Acute Setting and the Development of an Academic Criminological Career - Joseph Janes (Public Criminology, 2023)
This chapter reflects how participation in public criminological practice influenced my journey from undergraduate to doctoral study at Swansea University. As Burawo (2008) observes, students are the first public we face. My research has led to a process of self-reflection around notions of participation in the classroom, of shared experiences and a willingness to learn. Hearing young people talk openly about their futures, passions and dreams is powerful. It opens the door to a shared community, one in which Public Criminology offers added value. The chapter concludes by focusing on the dialogical nature of Public Criminology; the potential for the academy to drive social change; how Public Criminology can empower and transform the lives; and, how Criminology as a discipline is about much more than crime or criminal justice—it is about foundational social values and hope for better policy and practice.